Geological Analysis of Martian Rover‐Derived Digital Outcrop Models Using the 3‐D Visualization Tool, Planetary Robotics 3‐D Viewer—PRo3D. Issue 7 (20th July 2018) - Barnes, Robert; Gupta, Sanjeev; Traxler, Christoph; Ortner, Thomas; Bauer, Arnold; Hesina, Gerd; Paar, Gerhard; Huber, Ben; Juhart, Kathrin; Fritz, Laura; Nauschnegg, Bernhard; Muller, Jan‐Peter; et al.
Abstract: Panoramic camera systems on robots exploring the surface of Mars are used to collect images of terrain and rock outcrops which they encounter along their traverse. Image mosaics from these cameras are essential in mapping the surface geology and selecting locations for analysis by other instruments on the rover's payload. 2‐D images do not truly portray the depth of field of features within an image, nor their 3‐D geometry. This paper describes a new 3‐D visualization software tool for geological analysis of Martian rover‐derived Digital Outcrop Models created using photogrammetric processing of stereo‐images using the Planetary Robotics Vision Processing tool developed for 3‐D vision processing of ExoMars PanCam and Mars 2020 Mastcam‐Z data. Digital Outcrop Models are rendered in real time in the Planetary Robotics 3‐D Viewer PRo3D, allowing scientists to roam outcrops as in a terrestrial field campaign. Digitization of point, line, and polyline features is used for measuring the physical dimensions of geological features and communicating interpretations. Dip and strike of bedding and fractures is measured by digitizing a polyline along the contact or fracture trace, through which a best fit plane is plotted. The attitude of this plane is calculated in the software. Here we apply these tools to analysis of sedimentary rock outcrops and quantification of the geometry of fracture systems encountered by the science teams of NASA's Mars Exploration Rover Opportunity and Mars Science Laboratory rover Curiosity . We show the benefits PRo3D allows for visualization and collection of geological interpretations and analyses from rover‐derived stereo‐images. Plain Language Summary: Key data returned from robots exploring the surface of Mars are the images they take of the landscape and rock formations. These are sent back to Earth for detailed investigation and analysis by the science teams. It is difficult to collect reliable measurements from photographs, as they do not truly represent the three‐dimensionality of the features within them. In this paper, we present a new 3‐D visualization software tool, PRo3D, which enables visualization of 3‐D digital models of rock outcrops imaged by robots exploring the surface of Mars. These 3‐D models are constructed from mosaicked photographs taken by the stereo panoramic cameras which are positioned on a mast on the rover. This provides a huge advantage to scientists who want to study and analyze the terrain and geology of exposed rock outcrops which surround the rover. Here we apply the tools available in PRo3D to sedimentological and structural analysis of 3‐D Digital Outcrop Models of four areas explored by the Mars Exploration Rover Opportunity and Mars Science Laboratory Curiosity rover science teams and show that this method of 3‐D visualization and analysis allows scientists to carry out important procedures that would be conducted in a terrestrial field geology campaign. Key Points: Processing of images from stereo‐cameras on Mars rovers produces 3‐D Digital Outcrop Models (DOMs) which are rendered and analyzed in PRo3D PRo3D enables efficient, real‐time rendering and geological analysis of the DOMs, allowing extraction of large amounts of quantitative data Methodologies for sedimentological and structural DOM analyses in PRo3D are presented at four localities along the MSL and MER traverses